Monitoring the Environmental Factors of Endangered Plant Paphiopedilum Armeniacum - Jiang Xiao; Na Liang (Institute of Advanced Engineering and Science, 2013)
Paphiopedilum armeniacum is level-one protected species. As the original habitat destruction, Paphiopedilum armeniacum is at the brink of extinction now. In order to monitor the environment of the endangered plants such as Paphiopedilum armeniacum, to master the real-time changes of their environment factors such as temperature, humidity, light intensity, the design is based on AT89C51, regarded temperature, humidity and light intensity as the monitoring parameters, choosing temperature sensor DS18B20, humidity sensor HS1101, light-frequency converter TSL235 for data collection. The collection values of the environmental factors are displayed on light emitting diode, and the data transmission is fulfilled by using the PTR2000 short-range wireless transmission module. The micro control unit can accomplish joint factors monitoring such as temperature, humidity and light intensity. Now monitoring the environmental factors of Paphiopedilum armeniacum is a powerful move of protecting endangered plants, protecting the environment. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3580